Licensing digital content : a practical guide for librarians - Harris, Lesley Ellen (ALA editions., 2002)
As front line gatekeepers at the cutting edge of the digital revolution, librarians control how information is purchased, stored, and accessed. Complex laws and fast-changing practices in digital content licensing mean that every agreement starts from scratch, even as the availability of digital materials in the library increases exponentially. Covering the basics of digital licensing for librarians, this one-stop guide offers a practical, plain-language approach that demystifies the process. Copyright expert Lesley Ellen Harris shows--step-by-step--what it takes to negotiate and interpret solid.